Sociopragmatic Competence in EFL Academic Presentations: A Mixed-Methods Study of Science and Technology Students in Indonesia - Putri, Diannike; Kristanto, Barlian (English Education Department, 2025)
This study investigates the sociopragmatic competence of EFL learners in academic presentations within science and technology fields, specifically examining the gap between linguistic and interactive skills and the relationship between self-perception and actual performance. Using a mixed-methods approach, data were collected from 22 Indonesian EFL undergraduate students through a presentation performance assessment rubric evaluating five dimensions of sociopragmatic competence, complemented by a self-report questionnaire exploring participants' perceptions and experiences. The analysis revealed distinctive patterns of sociopragmatic competence, with participants demonstrating strengths in linguistic aspects but facing significant challenges in interactive components. A notable finding was the identification of a 'sociopragmatic competence paradox,' where strong linguistic skills did not necessarily translate to effective pragmatic competence in presentation contexts. The study also uncovered a significant gap between participants' high self-perception and lower actual performance in interactive aspects, alongside the substantial influence of anxiety and time management difficulties on sociopragmatic performance. These findings emphasize the need for a more holistic pedagogical approach in EFL teaching that integrates interactive skills development, anxiety management strategies, and metapragmatic awareness alongside traditional linguistic instruction. Keywords: sociopragmatic competence, EFL, academic presentations, science and technology, mixed methods